The sociology of health and illness critical perspectives - Conrad, Peter; Leiter, Valerie (SAGE Publications, Inc., 2024)
"This anthology for Medical Sociology courses, is edited by two leading experts in the field. It brings together readings from the scholarly literature on health, medicine, and health care, covering some of the most timely health issues of our day, including eating disorders, the effects of inequality on health, how race, class, and gender affect health outcomes, the health politics of asthma, the effects of health care reform, the pharmaceutical industry, health information on the Internet, and the impacts of the COVID-19 pandemic."